1984
DOI: 10.1246/cl.1984.603
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Diphosphenes With Elemental Selenium. Isolation and Characterization of Selenadiphosphiranes and Diselenoxophosphorane

Abstract: Sterically protected thermally stable 1,2,3-selenadiphosphirane and diselenoxophosphorane were isolated from the reaction of E-bis-(2,4,6-tri-t-butylphenyl) diphosphene with elemental selenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 12 publications
0
27
0
3
Order By: Relevance
“…Various double bonds of group 15-group 15 and group 14-group 15 elements have already been reported. As for the lowcoordinated double-bond compounds between group 15 and group 16 elements, dithioxophosphorane [RP(S)‫ס‬S] [2] and diselenoxo-phosphorane [RP(Se)‫ס‬Se] [3], have been synthesized as stable compounds, and thioxophosphines [RP‫ס‬S] [4] and selenoxophosphines [RP‫ס‬Se] [5] stabilized by the coordination of an amino group have been observed in solution by NMR spectroscopy. However, there are no reports about the double bond of antimony with sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…Various double bonds of group 15-group 15 and group 14-group 15 elements have already been reported. As for the lowcoordinated double-bond compounds between group 15 and group 16 elements, dithioxophosphorane [RP(S)‫ס‬S] [2] and diselenoxo-phosphorane [RP(Se)‫ס‬Se] [3], have been synthesized as stable compounds, and thioxophosphines [RP‫ס‬S] [4] and selenoxophosphines [RP‫ס‬Se] [5] stabilized by the coordination of an amino group have been observed in solution by NMR spectroscopy. However, there are no reports about the double bond of antimony with sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of 109 with Se-Et 3 N afforded the selenium analogs of 112 and 114 [114] The phosphine Ar*PH 2 produced the very stable dithioxophosphorane 114 by sulfurization with S 8 and 2,6-lutidine [116]. The synthesis of 114 was reported independently from several laboratories.…”
Section: From Phosphinidenes (R-p) To Kinetic Stabilization Of Low Comentioning
confidence: 99%
“…There are a several number of reports on the sulfurization and selenization reactions of diphosphenes [8,16,[18][19][20][21][22] and the related compounds bearing a low-coordinated phosphorus atom, that is, phosphaalkenes [23][24][25][26] and phosphinines [27][28][29]. It was demonstrated that the sulfurization and selenization reactions of diphosphenes should be convenient for obtaining unique heterocyclic compounds such as thia-and selenadiphosphiranes, since the sulfurization reaction of Mes * P PMes * using elemental sulfur in the presence of amine was reported to give the corresponding thiadiphosphirane, Mes * P(S)PMes (2d), as a stable three-membered heterocyclic compound via the corresponding diphosphene monosulfide, Mes * P P( S)Mes * as a metastable intermediate [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the sulfurization and selenization reactions of diphosphenes should be convenient for obtaining unique heterocyclic compounds such as thia-and selenadiphosphiranes, since the sulfurization reaction of Mes * P PMes * using elemental sulfur in the presence of amine was reported to give the corresponding thiadiphosphirane, Mes * P(S)PMes (2d), as a stable three-membered heterocyclic compound via the corresponding diphosphene monosulfide, Mes * P P( S)Mes * as a metastable intermediate [18,19]. For example, the synthesis of selenadiphosphiranes has been achieved by the treatment of diphosphenes (Mes * P PMes * , Mes * P PMes, Mes = 2,4,6-trimethylphenyl [22], and DisP PDis, Dis bis(trimethylsilyl)methyl [30]) with elemental selenium. We have also reported the syntheses and characterization of BbtP(Y)PBbt (Y = S (2c) and Se (3c)) by the chalcogenation reactions of hindered diphosphene, BbtP PBbt, using elemental sulfur and selenium [8,16].…”
Section: Introductionmentioning
confidence: 99%